* حديث * "يحمل هدا العلم من كل خلف عدوله" دراسة تحليلية - مقدادي, ميلود (University of eloued جامعة الوادي, 2016)
الحمد لله وحده والصلاة والسلام عمى من لا نبي بعده ىذه د ا رسة تحميمية لحديث: "يحمل ىذا العمم من كل خمف عدولو", و ان تجاذب صحة ىذا الحديث ونقد إسناده وحكم عميو جيابذة الفن بالضعف, فإن معنى الحديث والاستدلال بو لم أر من رده, إلا في حديثيم عن تعديل الرواة المسكوت عنيم, وغير ذلك فالحديث صحيح المعنى, وكل مواضيعو ومسائمو يشيد ليا الشرع بأصولو وأدلتو, فمرتبة العمماء التي أشار إلييا الحديث قد قررىا الكتاب العزيز, والسنة المطيرة, أما كشف أمر الإنتحال ووضع الحديث عن النبي صمى الله عميو وسمم, وتحريف الزنادقة, وتأ ويل الجاىمين, ومحاولاتيم الطعن في الدين بيذه الطريقة, فالأيام كفمت أمر إظياره لكل مسمم, وان دنت مرتبتو؛ أما جيد العمماء في كشفو والتصدي لو, فأدلتو آلاف الكتب, وآلاف الفتاوى والخطب, ولله در من تبوأ ىذه المرتبة, وخمف في الدفاع عن النبي صمى الله عميو وسمم وعن حياضو. والحمد لله أولا وآخر وصمى الله عمى نبينا محمد صمى الله عميو وسمماأفضل صلاة وأزكى تسميما .Praise be to god and alone peace be upon him , there is no prophet after . This is a study ,dissolwing for this talk "carry this knowledge the comig in succession and equal,certainly protract the validity of this talking , and criticise of his predication " . but the man of judgment this arts said it is weak talk ,assiduous talking and information ,I don't saw who give back it . If not in talking of equalisation narrators struck to him , another,but the talk true his assiduos , all object and problems is testify in the law , origin , information the platform of scientists , who speak this talk , and estabilish the noble book (quran) . and rule (sunnah) cleanliness . but to discover this order to be adopt and to make this speak to the prophet ,peace be upon him and to slawt from hypocrite , foolishness and trys of stabling in the religion by this way, but days to become , and clear for musulman . this order, untill to bached his platform but power of scientist discovered and shun , also,their information
علوم حذيث
Keywords: عدو/العلم//حديث; enemy/science//modern